Rancangan Aplikasi Wedding Organizer pada Sindy Salon Labuhanbatu Berbasis Web - Sari, Tukma (Journal of Computer Science and Information System(JCoInS), 2023)
During this time the wedding package information service at Cindy Salon and Decoration is done through recording on the order book. Recording in the order book is sufficient, but it is less effective and efficient because it cannot be processed into a report. In addition, the problem of checking transactions is more difficult. Therefore, a web-based wedding package ordering information system is needed at Cindy Salon and Decoration to improve service to customers. The purpose of making this information system is to be able to provide solutions to the problems mentioned above. This web-based wedding package ordering information system is expected to simplify the process of ordering wedding packages that are simple, easy and practical. This is needed especially to face competition in the world of wedding organizers. This information system can help disseminate information, manage ordering data, and make it easier for customers to order. This system is created using the PHP programming language and MySQL database server.